Poverty in bulgaria: dimensions, policies and analyses - Jeliazkova, Maria D. (Sociološki pregled, 2021)
The article discusses poverty in Bulgaria through the prism of the correspondence between the unfavorable wellbeing rates, the implemented policy’s measures and the state of analyses in the field. By presenting existing national and EU comparative statistics, analyzing policy documents and outlining limits and prevailing bias in the scientific research on the subject, it argues that the three aspects are functionally consistent and that overcoming the high levels of poverty in the country needs reconsidered and mobilizing actions aimed at: a) better consistency among policies in different fields (economic, social, tax, insurance, labor market, environmental, etc.); and b) knowledge-based development focused on adequate addressing of structural generators of poverty.
Keywords: poverty indicators; distributive and redistributive policies; active labor market measures; social assistance; anti-poverty strategy